Efficient Solution‐Processed Bulk Heterojunction Perovskite Hybrid Solar Cells. Issue 12 (9th April 2015) - Liu, Chang; Wang, Kai; Du, Pengcheng; Yi, Chao; Meng, Tianyu; Gong, Xiong
<x xml:space="preserve">Abstract</x> Efficient conventional bulk heterojunction (BHJ) perovskite hybrid solar cells (pero‐HSCs) solution‐processed from a composite of CH3NH3PbI3 mixed with PC61BM ([6, 6]‐phenyl‐C61‐butyric acid methyl ester), where CH3NH3PbI3 acts as the electron donor and PC61BM acts as the electron acceptor, are reported for the first time. The efficiency of 12.78% is twofold enhancement in comparison with the conventional planar heterojunction pero‐HSCs (6.90%) fabricated by pristine CH3NH3PbI3. The BHJ pero‐HSCs are further optimized by using PC61BM/TiO2 bi‐electron‐extraction‐layer (EEL), which are both solution‐processed and then followed with low‐temperature thermal annealing. Due to higher electrical conductivity of PC61BM over that of TiO2, an efficiency of 14.98%, the highest reported efficiency for the pero‐HSCs without incorporating high‐temperature‐processed mesoporous TiO2 and Al2O3 as the EEL and insulating scaffold, is observed from PC61BM modified BHJ pero‐HSCs. Thus, the findings provide a simple way to approach high efficiency low‐cost pero‐HSCs.